Operational Model to Improve Productivity by Applying Lean Manufacturing and Circular Economy in an Agricultural SME - Mansilla Blanco, Johana; Saldaña Romero, Leslie; Chavez-Ugaz, Rafael (LACCEI, 2024)
Agriculture is essential for sustainability and economic development due to growing demand for food and natural resources. In Peru, the industry has seen recent growth and is crucial for national advancement; however, it faces issues related with low productivity. Specifically, Peruvian agriculture SMEs have labor productivity lower than the average, significant food losses during storage and processing activities, as well as inefficient usage of irrigation water. A case study of a Peruvian company focused on agricultural exports, especially grape production, revealed a productivity rate of 0.77 kilograms of exportable grapes per kilogram of harvested grapes, below the industry standard of 0.85. The research aims to improve productivity of the exportable grapes processes by implementing an Operational Model that integrates lean principles, such as 5S, Standard Work, Kaizen, and Value Stream Mapping, with Circular Economy strategies including 3Rs and Life Cycle Assessment. To verify the effectiveness of the proposed model, the methodology included pilot tests implementations for lean tools and Montecarlo simulation for 3Rs, followed by an integrated simulation in Arena to obtain the final outputs. Results achieved expectations, achieving a 75.59% reduction in water footprint, reducing grape losses to 1.17% and improving the Food Loss Index by 58.31%. Additionally, labor productivity improved with a 38.50% reduction in average worker time for packing activities, resulting in an overall productivity increase to 0.85 kilograms of exportable grapes per kilogram harvested, meeting industry standards. Future research should address seasonal variability, consider reusing tools for irrigation, and conduct feasibility studies to improve storage technologies.